Design and Numerical Simulation of Pyramidal Prefolded Patterned Thin-Walled Tubes - Junxian Zhou; Chuang Dong; Bingzhi Chen; Xu Niu (Advances in Materials Science and Engineering)
An improved pyramidal prefolded pattern was designed and applied to thin-walled tubes. This delicately designed pattern modularizes the tube to control the folding process and act as an inducer to trigger deformation modes with outstanding crushing performance. Dynamic crushing tests were conducted numerically; the simulation results reveal that the patterned square tube developed a deformation mode with shorter wavelength, better load consistencies, and higher energy-absorption efficiency (up to 29%) than that of the traditional counterpart. Moreover, geometric analysis was performed and structural improvements were conducted by applying the optimal geometric parameters onto an octagonal profile. The designed patterned octagonal tube collapsed into a highly efficient deformation mode known as diamond mode. Furthermore, the comparative results show that patterned octagonal tubes demonstrated an energy absorption up to 90.1% higher than that of a conventional square column while improving the geometric compliance. These findings enrich research on patterned tubes and provide new explorations for the development of high-performance energy-absorbing structures.